Azithromycin and the Risk of Cardiovascular Complications. (October 2014) - Maisch, Nicole M.; Kochupurackal, Jenny G.; Sin, Jonathan
The purpose of this review was to evaluate the literature to assess the incidence and true clinical relevance of recent Food and Drug Administration warnings regarding QT prolongation with azithromycin, given its widespread use, with over 40 million US outpatient prescriptions written in 2011. A literature search of MEDLINE (1946 to May 2013) and International Pharmaceutical Abstracts (1970 to May 2013) was conducted using the terms azithromycin, QT prolongation, torsades de pointes, arrhythmia, and cardiovascular death. A bibliographic search was also performed. Several relevant studies and case reports were identified and reviewed. One cohort study revealed an increased risk of cardiovascular death with azithromycin compared to no antibiotic, especially in those with higher cardiovascular risk. Another cohort study comparing azithromycin, penicillin V, and no antibiotic in a younger Danish population with less cardiac risk found no increased cardiovascular death associated with azithromycin use. The majority of case reports involved ill and/or elderly patients with multiple comorbidities and concomitant medications who were already at a higher risk of cardiovascular events. Although there is evidence that azithromycin may induce QT prolongation and adverse cardiac events, the incidence is fairly limited to patients with high baseline risk, including those with preexisting cardiovascular conditions and concomitant use of other QT-prolonging drugs.